Assessing the effects of a two-amino acid flexibility in the Hemagglutinin 220-loop receptor-binding domain on the fitness of Influenza A(H9N2) viruses. Issue 1 (1st January 2021) - Sun, Yixue; Cong, Yulin; Yu, Haiying; Ding, Zhuang; Cong, Yanlong
ABSTRACT: The enzootic and zoonotic nature of H9N2 avian influenza viruses poses a persistent threat to the global poultry industry and public health. In particular, the emerging sublineage h9.4.2.5 of H9N2 viruses has drawn great attention. In this study, we determined the effects of the flexibility at residues 226 and 227 in the hemagglutinin on the receptor avidity and immune evasion of H9N2 viruses. The solid-phase direct binding assay showed that residue 226 plays a core role in the receptor preference of H9N2 viruses, while residue 227 affects the preference of the virus for a receptor. Consequently, each of these two successive residues can modulate the receptor avidity of H9N2 viruses and influence their potential of zoonotic infection. The antigenic map based on the cross-hemagglutination inhibition (HI) titers revealed that amino acid substitutions at positions 226 or 227 appear to be involved in antigenic drift, potentially resulting in the emergence of H9N2 immune evasion mutants. Further analysis suggested that increased receptor avidity facilitated by residue 226Q or 227M resulted in a reduction in the HI titer. Among the four naturally-occurring amino acid combinations comprising QQ, MQ, LQ, and LM, the number of viruses with LM accounted for 79.64% of the sublineage h9.4.2.5 and the rescued virus with LM exhibited absolute advantages of in vitro and in vivo replication and transmission. Collectively, these data demonstrate that residues 226 and 227 are under selective pressure and their synergistic regulation of receptor avidity and antigenicity is related to the evolution of circulating H9N2 viruses.